Delivery Route Considerations for Designing Antigen‐Specific Biomaterial Strategies to Combat Autoimmunity. Issue 3 (29th January 2023) - Ackun-Farmmer, Marian A.; Jewell, Christopher M.
Abstract : Disease‐modifying drugs and biologics used to treat autoimmune diseases, although promising, are non‐curative. As the field moves toward development of new approaches to treat autoimmune disease, antigen‐specific immunotherapies (ASITs) have emerged. Despite clinical approval of ASITs for allergies, clinical trials using soluble ASITs for autoimmunity have been largely unsuccessful. A major effort to address this shortcoming is the use of biomaterials to harness the unique features of specific delivery routes. This review focuses on biomaterials delivery route considerations to induce antigen‐specific responses in autoimmune diseases such as multiple sclerosis, type 1 diabetes, rheumatoid arthritis, and celiac disease. The delivery strategies used in ongoing and completed clinical trials in autoimmune ASITs are first discussed. Next, preclinical biomaterial approaches from the most recent 3 years in the context of these same delivery route considerations are highlighted. Finally, discussion on the gaps remaining in biomaterials development is provided and the need to consider delivery routes in the process of designing biomaterials for ASITs is commented on. Abstract : Biomaterials‐based antigen‐specific immunotherapies (ASITs) for treating autoimmunity offer unique features to control the presentation and delivery of disease‐relevant antigens and regulatory immune cues. This article summarizes why some delivery routes used for ASITs work better than others, summarizes the delivery routes used in ASIT clinical trials, and discusses delivery routes used by current experimental biomaterials‐based ASITs.